Preliminary data indicating a connection between stress-induced prefrontal dopamine release and hippocampal TSPO expression in the psychosis spectrum - Schifani, Christin (Schizophr Res, 2018)
Prolonged stress can cause neuronal loss in the hippocampus resulting in disinhibition of glutamatergic neurons proposed to enhance dopaminergic firing in subcortical regions including striatal areas. Supporting this, imaging studies show increased striatal dopamine release in response to psychosocial stress in healthy individuals with low childhood maternal care, individuals at clinical high risk for psychosis (CHR) and patients with schizophrenia. The prefrontal cortex (PFC) is connected to the hippocampus and a key region to control neurochemical responses to stressful stimuli. We recently reported a disrupted PFC dopaminestress regulation in schizophrenia, which was intact in CHR. Given the available evidence on the link between psychosocial stress, PFC dopamine release and hippocampal immune activation in psychosis, we explored, for the first time in vivo, whether stress-induced PFC dopamine release is associated with hippocampal TSPO expression (a neuroimmune marker) in the psychosis spectrum. We used an overlapping sample of antipsychotic-naive subjects with CHR (n=6) and antipsychotic-free schizophrenia patients (n=9) from our previously published studies, measuring PFC dopamine release induced by a psychosocial stress task with [(11)C]FLB457 positron emission tomography (PET) and TSPO expression with [(18)F]FEPPA PET. We observed that participants on the psychosis spectrum with lower stress-induced dopamine release in PFC had significantly higher TSPO expression in hippocampus (P =−2.39, SE=0.96, F(1,11)=6.17, p=0.030). Additionally, we report a positive association between stress-induced PFC dopamine release, controlled for hippocampal TSPO expression, and Global Assessment of Functioning. This is the first exploration of the relationship between PFC dopamine release and hippocampal TSPO expression in vivo in humans.